Issues Faced by the Cochlear Implanted Students in the Mainstream Classes: An Analysis of Perspectival Accounts of Primary School Teachers - Qurratulain Ershad; Dr. Sumaira Noreen (Research Journal of Social Sciences and Economics Review, 2020)
Learning to write is developmentally essential for nurturing literate children; its inability creates a huge barrier so is true for cochlear implanted students who face several challenges in terms of literacy and language development proficiency. It is a big challenge for any child with any kind of disability especially a listening disability to cope in the mainstream classroom with their peers and the communities where they live. And so is true for teachers of mainstream classes in their efforts towards classroom learning in a comfortable environment for such students. These papers aim at investigating perceptions and the problems faced by the primary teachers while teaching CI students in the mainstream classes. The study adopted qualitative methodology and the sample was purposively selected comprising of seven primary teachers who had CI students in their respective classes and were teaching them. Semi-structured interviews to determine the perceptions and the problems they encounter during the teaching-learning process. The semi-structured interview schedule consisted of twenty-four questions that were grouped into four major themes of the study. The results highlighted the importance of teachers' awareness, their training, and the use of differentiated instructions to help CI learners to cope in the mainstream classroom to their maximum potential.